Bifurcated outflow jet in a solar wind reconnection exhaust - Liu, Chaoxu; Feng, Xueshang; Guo, Jianpeng; Fu, Huiyuan (Astrophysics and space science, 2021)
We present new observations of the reconnection outflow jet obtained from the crossing of a solar wind reconnection exhaust by the Wind spacecraft on 5 March 2001. The outflow jet is characterized by a bifurcated configuration, which is different from typical reconnection exhausts. The two outflow jets are mainly distributed in the region close to the exhaust boundaries. Between the two jets, the bulging of the magnetic field and the slight depression of the plasma density are observed. The possible mechanism for the bifurcation of the outflow jet has also been investigated by using a magnetohydrodynamics (MHD) simulation of Petschek-type reconnection. The dynamic patterns of the reconnection exhaust are analyzed in detail. We find that the bifurcated jet is one of the transient configurations produced in the magnetic reconnection. Other observed features of the exhaust show similar agreement with the predictions from the simulation. The study of the reconnection exhaust, over multiple spatial scales, provides an insight into the dynamic evolution of solar wind reconnection exhausts.